Students Adjustment to College: Quantitative Study of Physical Education Students in 2023 - Arwin; Bayu Insanistyo; Yahya Eko Nopiyanto; Ibrahim; Ipa Sari Kardi (Indonesian Journal of Physical Education and Sport Science)
Study purpose. Adaptation is very important for student development, especially in the academic field. This study aims to describe the level of ability of physical education students in adapting to the academic environment in 2023.